Cold recovery from LNG-regasification for polygeneration applications. (5th March 2018) - Atienza-Márquez, Antonio; Bruno, Joan Carles; Coronas, Alberto
Highlights: The cold recovery in the LNG regasification is a valuable exergy source. Current applications and technologies for LNG cold recovery are reviewed. LNG cold can be efficiently exploited via polygeneration. A polygeneration plant for cold recovery from LNG-regasification is analyzed. An energy saving of 81.1 kW h/ton-LNG and a seawater saving of 67.6% are obtained. Abstract: Liquefied Natural Gas (LNG) has a high exergetic potential because of its low temperature (around −162 °C), although usually the cold released from LNG regasification is wasted. In this paper, the LNG supply chain and the conventional regasification technologies are reviewed and analyzed to identify the cold recovery opportunities. Also, an overview of the applications and technologies for LNG cold recovery is presented. Although there many applications and technologies for this purpose, most of them are immatures and their implementation is not widespread. Besides, most of the literature is focused on exploiting LNG cold for a single application, while LNG cold offers a lot of possibilities of exploitation via polygeneration. In the second part of this paper, a polygeneration plant for power and cold production is proposed and modelled as a case study for cold recovery from LNG-regasification. The structure of the plant is engineered to operate with high flexibility. The LNG exergy is exploited in cascade for power production and cold generation in a district cooling network with three different temperature levels. The plant achieves an equivalent energy saving of 81.1 kW h/ton-LNG with an exergetic efficiency of 34.7%. The seawater consumption is reduced 67.6% respect to the typical LNG regasification.